LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING DALAM MENGURANGI BURNOUT (KEJENUHAN) BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 3 CIPATAT - Melisa Restiastuti; Hidayat, Wahyu; Ayu Ningrum, Devy Sekar (IKIP Siliwangi, 2024)
This study aims to describe the effectiveness of group counseling services using role playing techniques in reducing burnout in class VIII students at SMP Negeri 3 Cipatat. The variables in this study were group guidance with role playing techniques and learning burnout. The burnout theory used is based on the theory of Maslach and Jackson (1981). The research method used is a mixed method with an explanatory sequential design. Sampling in this study using purposive sampling technique. The sample in this study was 10 class VIII students. Quantitative data were collected through questionnaires (pretest and posttest) and analyzed by T-test while qualitative data were collected through observation and interviews which were analyzed using data reduction. The results of the quantitative data showed that there was a decrease in student learning burnout through group guidance services. role playing technique with a significance value (2-tailed) 0.000 <0.05. So it can be concluded that group guidance services with role playing techniques are effective in reducing learning burnout for class VIII students of SMP Negeri 3 Cipatat. From the results of qualitative data, it shows that there are obstacles from students and counseling teachers.